National logistics working groups: A landscape analysis study. Issue 17 (19th April 2017) - Leab, Dorothy; Schreiber, Benjamin; Kasonde, Musonda; Bessat, Olivia; Bui, Son; Loisel, Carine
Abstract: Several countries have acknowledged the contributions made by national logistics working groups (NLWG) to ensure equitable access to the expanded program on immunization's (EPI) vaccines against preventable diseases. In order to provide key insights to the United Nations Children's Fund (UNICEF) and the World Health Organization (WHO) supply chain hub – as well as other players, including national EPI – a landscape analysis study was conducted from September 2015 to February 2016. This is a cross-sectional survey taken by 43 countries that combines qualitative and quantitative approaches. Data was collected through a desk review, consultation, interviews, and distance questioning. References and guidance were used to determine and specify the underlying mechanisms of NLWGs. The key findings are: Mandate of NLWG commonly declared by countries is improving immunization logistics and supply chain. Of the 43 countries surveyed, 10 have formal NLWGs, 8 have informal or ad hoc NLWGs, and 25 have none. The immunization supply chain and logistics (iSCL) decision-making process in countries, regardless of NLWG status, mainly depends on the EPI manager. In countries with an NLWG, members with logistics and supply chain backgrounds are relatively common; they are mostly from EPI, UNICEF, and WHO. Almost all NLWGs have terms of reference and primarily operate under EPI governance; however, three NLWGs have standard operation procedures (SOP), and four use monitoring and evaluation tools. The coordination mechanism of these iSCL activities is mainly built into the immunization Comprehensive Multi-Year Plan (cMYP) and annual EPI plans, and organized by EPI/Immunization Coordination Committee (ICC). Most countries that participated in this survey expressed their technical requirement for improving the function, positioning and influence of the immunization logistics working group, and capacity building for the group's members. This study has provided a general overview of the status of NLWGs for immunization in various countries. Based on the key insights of the study, technical assistance needs have been identified, and immunization partners will be required to help countries create and reinforce their NLWGs.